Efektivitas Edukasi Gizi Komunitas untuk Meningkatkan Pengetahuan Ibu dan Kader dalam Pencegahan Tuberkulosis Anak - Aprina, Aprina; Bustami, Anita; Astuti, Titi (SEGANTANG LADA : JURNAL PENGABDIAN KESEHATAN, 2025)
Childhood Pulmonary Tuberculosis (TB) remains a critical public health challenge in Indonesia, particularly in Sidodadi Village, Pringsewu Regency, Lampung. Community members and health cadres often lack sufficient understanding of  balanced nutrition as a preventive strategy against TB. This community engagement program aimed to improve the knowledge of mothers with toddlers and health cadres regarding child nutrition for TB prevention. The intervention included an initial survey, development of educational modules, interactive sessions for 20 families, targeted training for 20 health cadres, mentoring, and evaluation using pre-tests, post-tests, questionnaires, and observation. Results indicated a significant improvement in knowledge: from 50% to 82% in the mothers’ group,  and from 62% to 90% among health cadres. These improvements were attributed to interactive learning methods and the pivotal role of health cadres as agents of behavioral change, aligning with Social Cognitive Learning Theory. The program effectively enhanced knowledge capacity and has the potential to influence family nutrition practices and reduce the incidence of childhood TB. Recommendations include sustained mentoring, long-term impact evaluation, and development of advanced training modules for health cadres.